2010
DOI: 10.1002/anie.201001298
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Cyclic Voltammetry of Immobilized Azurin: Direct Observation of Thermodynamic and Kinetic Heterogeneity

Abstract: Variations in the formal electrochemical potential (E0) and electron‐transfer rates (k0) of the blue copper protein azurin have been directly observed. A new method, fluorescent cyclic voltammetry (FCV), was used to resolve the properties of 100–1000 proteins. On this scale, the presence of large variations in the values of both E0 and k0 could be established and several forms of heterogeneity were differentiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 45 publications
10
99
3
Order By: Relevance
“…However, we can see that using these lower values of k 0 compared to those reported experimentally by Salverda et al 20 …”
Section: ■ Theorycontrasting
confidence: 62%
See 1 more Smart Citation
“…However, we can see that using these lower values of k 0 compared to those reported experimentally by Salverda et al 20 …”
Section: ■ Theorycontrasting
confidence: 62%
“…This situation applies to about half of the molecules in the distribution given in Figure 2(b). If some of the k 0 values for the dispersion distribution within a simulation are at, or exceed, the reversible limit that applies to the scan rate Indeed, if we repeat the simulations with weights adapted from the k 0 distribution reported in Figure 2(b), 20 with E 0 still fixed, then we recover a half-height width value of W 1/2 = 99 mV, contrasting with W 1/2 = 90 mV with no dispersion included or with the value W 1/2 = 89 mV predicted for a fully reversible process. Thus, kinetic dispersion under the conditions assumed has a much larger impact than thermodynamic dispersion.…”
Section: Results In Significant Increases In W 1/2 Valuesmentioning
confidence: 99%
“…Thin layer of MoGe was deposited at a rate of 1.32 nm/min under 10 mtorr Argon environment, whereas gold deposition was carried out at a rate of 9.06 nm/min under Argon and oxygen environment (10 mTorr Argon and 1mTorr Oxygen). The root mean square roughness of the deposited films was 2-3 Å (Akkilic et al, 2014;Salverda et al, 2010).…”
Section: Preparation Of Gold Electrodementioning
confidence: 99%
“…It has been already shown that wild type of azurin (Pseudomonas aeruginosa) can be adsorbed through exposed hydrophobic residues on a methylterminated alkanthiol SAM [3,4,[6][7][8]. The effect of SAM length on the ET kinetics of azurin has been studied [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…Second, SAM-modified electrodes provide an ability to study fast electron transfer (ET) of the proteins by removing their sluggish diffusion [3]. Third, SAM-modified electrodes pave the way for protein investigation with high sensitivity in trace amounts [4]. Lastly, it is possible to have a control-over-orientation of immobilized protein, by using different functional groups on the SAM [5].…”
Section: Introductionmentioning
confidence: 99%